Characterization of a micro thermal cavity receiver – Experimental and analytical investigation. (1st August 2020) - Daabo, Ahmed M.; Bellos, Evangelos; Pavlovic, Sasa; Bashir, Muhammad Anser; Mahmoud, Saad; Al-Dadah, Raya K.
Highlights: Experimental investigation of a small scale cavity receiver is performed. A numerical model is developed for the thermal analysis of the receiver. The operating working fluid is compressed air. The aspect ratio of the cavity is an important parameter of this work. The thermally optimum cavity depth is 180 mm and width 240 mm. Abstract: The objective of this work is to characterize the optical and thermal performance of a micro-scale cylindrical cavity solar receiver for the Brayton gas power cycle at various solar radiation levels through experimental and analytical investigation. A thermal receiver consisting of a 300 mm deep and 200 mm diameter cylindrical cavity equipped with an 8 mm diameter helical copper tube was studied. An advanced ray-tracing technique using OptisWorks software was used to predict the distribution of solar radiation inside the cavity. Also, computational fluid dynamics simulations were carried out using ANSYS CFD software to predict the temperature distributions of the coil surface and the compressed air outlet temperature. Having satisfying conformity between the numerical and the experimental results, the current results demonstrated that a competent flux and temperature distributions were directed on the receiver's tube. Moreover, an outlet temperature up to 70 °C, based on the available compressed air flow rate. This point leads to the probability of operating a micro-scale dish concentrator for Concentrated Solar Power in a domestic application. The results of a parametric study indicated that a cavity's receiver depth and width of 180 mm and 240 mm give the best thermal operation.